2008
DOI: 10.1038/sj.ejcn.1602980
|View full text |Cite
|
Sign up to set email alerts
|

Resting energy expenditure can be assessed by dual-energy X-ray absorptiometry in women regardless of age and fitness

Abstract: Objective: To evaluate the possibility that measurement of the magnitude and distribution of fundamental somatic heatproducing units using dual-energy X-ray absorptiometry (DXA) can be used to estimate resting energy expenditure (REE) in both young and elderly women with different aerobic fitness levels. Subjects and methods: Peak oxygen uptake (VO 2 peak) and REE m were directly measured in 116 young (age: 22.3±2.1 years) and 72 elderly (63.3 ± 6.4 years) women. The subjects were divided into four groups acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…However, we demonstrated that estimation based on the four tissue organs by using DXA allows successful calculation of REE in female adults regardless of age and aerobic fitness levels. (Usui et al, 2009). Our findings suggested the possibility that REE is regulated mainly by the mass of the tissue organs with lower and higher metabolic rates, including skeletal muscle and intestinal organs, rather than a decline in the specific metabolic rate of different tissue organs associated with advancing age and decreasing aerobic fitness levels in young and elderly women.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…However, we demonstrated that estimation based on the four tissue organs by using DXA allows successful calculation of REE in female adults regardless of age and aerobic fitness levels. (Usui et al, 2009). Our findings suggested the possibility that REE is regulated mainly by the mass of the tissue organs with lower and higher metabolic rates, including skeletal muscle and intestinal organs, rather than a decline in the specific metabolic rate of different tissue organs associated with advancing age and decreasing aerobic fitness levels in young and elderly women.…”
Section: Discussionmentioning
confidence: 84%
“…REE = k 1 ×tissue organ mass 1 + k 2 ×tissue organ mass 2 + k 3 ×tissue organ mass 3 + ··· Dual-energy X-ray absorptiometry (DXA) can easily and accurately assess the body composition, including bone mineral content (BMC), fat mass (FM), and lean soft tissue mass (LST) of the whole body and the segments (Mazes et al, 1990;Svendsen et al, 1991Svendsen et al, & 1993. In addition, recent studies support the use of DXA as a means of providing a "metabolic map" for exploring between individual or group differences in observed REE values (Hunter et al, 2001;Hayes et al, 2002;Usui et al, 2009). Specifically, the LST of the arms and legs, as provided by regional DXA estimates, represents primarily lowmetabolic rate skeletal muscle tissue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The body mass index (BMI) was calculated by dividing BW in kilograms by the square of Ht in meters (kg/m 2 ). Dual-energy X-ray absorptiometry (DXA) (Hologic QDT-4500, DXA Scanner, Hologic Inc., Whaltham, MA, USA), a relatively easy and non-invasive technique ( 11 ), was used to measure bone mineral content (BMC) (g), lean soft tissue mass (g), and % body fat. FFM and fat mass (FM) were then calculated based on BW and % body fat.…”
Section: Subjectsmentioning
confidence: 99%